2013
DOI: 10.1016/j.clinthera.2013.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Naloxegol on Cardiac Repolarization: A Randomized, Placebo- and Positive-Controlled Crossover Thorough QT/QTc Study in Healthy Volunteers

Abstract: Naloxegol at 25 and 150 mg was not associated with QT/QTc interval prolongation in these healthy men, and at the proposed therapeutic dose of 25 mg/d, naloxegol is not expected to have a clinically relevant effect on cardiac repolarization in patients with OIC. ClinicalTrials.gov identifier: NCT01325415.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…11 The mean C max for moxifloxacin reached 2115.5 ng/mL in this study, a value that is slightly lower than previous reports 6 but consistent with values reported for recently conducted Thorough QT/QTc studies. 12,13 Peak concentrations of moxifloxacin were rapidly achieved, with a t max value of 2.24 hours; this value is also consistent with the timing of the ECG measurements (1, 2, and 3 hours after dosing), suggesting that ECG measurements likely occurred very near the peak plasma concentrations. Interestingly, an initial peak increase in the ΔΔQTcF interval was observed at 4 hours after dosing, which was 2 hours after tmax; however, as is evident from the observed linear concentration-QTcF association modeling, there is an apparent association between plasma concentrations and ΔΔQTcF.…”
Section: Discussionsupporting
confidence: 72%
“…11 The mean C max for moxifloxacin reached 2115.5 ng/mL in this study, a value that is slightly lower than previous reports 6 but consistent with values reported for recently conducted Thorough QT/QTc studies. 12,13 Peak concentrations of moxifloxacin were rapidly achieved, with a t max value of 2.24 hours; this value is also consistent with the timing of the ECG measurements (1, 2, and 3 hours after dosing), suggesting that ECG measurements likely occurred very near the peak plasma concentrations. Interestingly, an initial peak increase in the ΔΔQTcF interval was observed at 4 hours after dosing, which was 2 hours after tmax; however, as is evident from the observed linear concentration-QTcF association modeling, there is an apparent association between plasma concentrations and ΔΔQTcF.…”
Section: Discussionsupporting
confidence: 72%
“…Most frequently reported AEs were transient GI complaints, typically resolving within the first week, and often reported as mild or moderate. No clinical relevant changes in serum chemistry, hematology, or electrocardiogram were revealed, confirming the results from two Phase I studies 97,98. There was no significant reduction of opioid-mediated analgesia.…”
Section: Naloxegol – Pegylated Naloxonesupporting
confidence: 79%
“…These studies used an oral solution, but an oral tablet formulation was shown to have similar pharmacokinetic properties [26]. In a thorough QT study in healthy volunteers, acute doses of naloxegol of 25 or 150 mg showed no signs QT prolongation [27].…”
Section: Human Pharmacodynamic Studiesmentioning
confidence: 99%